2015
DOI: 10.1016/j.biomaterials.2015.04.055
|View full text |Cite
|
Sign up to set email alerts
|

c-Kit+ progenitors generate vascular cells for tissue-engineered grafts through modulation of the Wnt/Klf4 pathway

Abstract: The development of decellularised scaffolds for small diameter vascular grafts is hampered by their limited patency, due to the lack of luminal cell coverage by endothelial cells (EC) and to the low tone of the vessel due to absence of a contractile smooth muscle cells (SMC). In this study, we identify a population of vascular progenitor c-Kit+/Sca-1- cells available in large numbers and derived from immuno-privileged embryonic stem cells (ESCs). We also define an efficient and controlled differentiation proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…In this study, using the model of iPS‐ECs generation, FSTL3 expression was found to be upregulated by KLF4 , a key mediator of EC differentiation . In addition, FSTL3 expression progressively increased throughout the iPS‐ECs generation process, highlighting a likely angiogenic role.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In this study, using the model of iPS‐ECs generation, FSTL3 expression was found to be upregulated by KLF4 , a key mediator of EC differentiation . In addition, FSTL3 expression progressively increased throughout the iPS‐ECs generation process, highlighting a likely angiogenic role.…”
Section: Discussionmentioning
confidence: 70%
“…A). We and others have previously shown that KLF4 is implicated in EC differentiation from pluripotent stem cells. In our iPS‐ECs system, it was confirmed that KLF4 was increased during EC differentiation, with a concomitant decrease of the pluripotent marker OCT4 (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…When such engineered vessels were grafted in vivo , they demonstrated better patency than cell‐free scaffolds . A recent study utilized embryonic stem cell‐derived c‐kit+ cells as a source for SMCs and ECs and got encouraging results, with increased patency of in vivo grafted vessels for the generation of bioengineered vascular grafts . However, the application of embryonic stem cells is largely hampered by ethical concerns and induced pluripotent stem cells require the transfection of pluripotency factors often via viral delivery.…”
Section: Animal Studies and Clinical Trials Using Mscs For Vascular Rmentioning
confidence: 99%
“…Distinct endothelial lineages have considerable differences regarding their transcriptome, and the extent of endothelial cell heterogeneity is currently a matter of debate [17][18][19]. Nevertheless, endothelial identity is mandatory to control vascular tone and for the paracrine regulation of vascular specification within the graft [20][21][22]. Accordingly, transcriptomic signatures of pre-seeded endothelial cells (EC) should correspond to those of mature resident EC.…”
mentioning
confidence: 99%